Approach to chemotherapy-associated thrombosis. (April 2015) - Oppelt, Peter; Betbadal, Anthony; Nayak, Lalitha
Treatment of cancer patients with antineoplastic agents is associated with a heightened risk of thrombotic events, both arterial and venous. In this article, we review the specific agents that are implicated and the pathophysiological processes that are known to be associated with this prothrombotic state. We conclude with current recommendations for prophylactic antithrombotic therapy in these clinical situations.